The Polarization of Bondowoso Hadhramis and Their Intra-Ethnic Relations - Bahar, Moh Syaeful; Ali, Ahmad Khubby; Harnadi, Dodik (AL-TAHRIR, 2023)
This article examines polarization within the Hadhrami Arab population in Bondowoso, East Java, especially in light of the rise of the 212 movement and the presidential election in 2019. During this time, the national political climate has become more tense. The issue of religion, which is drawn to political contestation, creates polarization among Muslims, including Arab Muslims. In Bondowoso, the polarization aligns with the different religious understanding backgrounds such as Sunni and Shi’a.  Nevertheless, polarization does not lead to social conflicts between them. Departing from this description, this study then focuses on two things. First, it seeks to reveal the views of Hadhrami Arabs on several national issues based on their respective religious backgrounds. Second, this study also reveals Arab intra-ethnic relations with different positions in addressing national issues. This research applied qualitative research with a case study approach to examine this focus. The study found that Arab perceptions of national issues varied according to their religious background. These perceptions correspond to their respective religious understanding. Second, although they differ in political and religious positions, the internal relations among Bondowoso Arabs are running normally without falling into violent conflict.